Aviation-induced cirrus and radiation changes at diurnal timescales - Schumann, Ulrich; Graf, Kaspar (Journal of Geophysical Research: Atmospheres, 2013)
The radiative forcing from aviation-induced cirrus is derived from observations and models. The annual-mean diurnal cycle of airtraffic in the North Atlantic region (NAR) exhibits two peaks in early morning and afternoon with different peak times in the western and eastern parts of the NAR. The same "aviation fingerprint" is found in eight years (2004-2011) of Meteosat observations of cirrus cover and outgoing longwave radiation (OLR). The observations are related to airtraffic data with linear response models assuming the background atmosphere without aviation to be similar to that observed in the South Atlantic. The change in OLR is interpreted as aviation-induced longwave radiative forcing (LW RF). The data analysis suggests a LW RF of about 600—900 mW m-2 regionally. A detailed contrail-cirrus model for given global meteorology and airtraffic in 2006 gives similar results. The global RF is estimated from the ratio of global and regional RF as derived from three models. The extrapolation implies about 100--160 mW m-2 global LW RF. The models show large differences in the shortwave/longwave RF-magnitude ratio. One model computes a ratio of 0.6, implying an estimate of global net RF of about 50 (40-80) mW m-2. Other models suggest smaller ratios, with less cooling during day, which would imply considerably larger net effects. The sensitivity of the results to the accuracy of the observations, traffic data, models and the estimated background is discussed.